IMPLEMENTATION DIVERSION IN SETTLEMENT CASES FOR CHILDREN PERPETRATORS CRIME THEFT AT TANJUNG KARANG DISTRICT COURT - Daffa Ladro Kusworo; Maghfira Nur Khaliza Fauzi (Universitas Lampung, 2023)
The implementation of Diversion solves children's cases with peace efforts outside the judicial process and always provides legal protection to children to fulfill their future interests. In the data obtained that the implementation of Diversion in the settlement of cases of child perpetrators of the crime of theft in 2022, the Tanjung Karang District Court has succeeded in carrying out diversion cases in 3 cases out of 11 cases theft. However, there was a failure in carrying out Diversion because only one of them was successfully handled by Diversion, indicating that obstacles were found that affected the success of the Diversion. This study uses normative Law accompanied by legal rules that apply in society and literature studies in the form of books, journals, etc. The analytical method that will be used for this normative legal research is to use qualitative analysis methods. The data from this qualitative analysis are obtained from various sources in qualitative research; data analysis is more focused during the process in the field and data collection. It can be concluded that obstacles affect the success of Diversion at the Tanjung Karang District Court because the victim does not agree to the diversion agreement. There are objections to the compensation fee that the perpetrator must make to the victim and different understandings of law enforcement officials (APH) to implement Diversion successfully.